Optimization of Bicycle Frame Design With Variation of Materials - Amir; Muchammad Chusnan Aprianto; Sukarman; Dodi Mulyadi; Muhammad Rahmantio Septiana (TURBO [Tulisan Riset Berbasis Online], 2026)
This study shows how to model the best results of several bicycle frame designs with a variety of materials. The use of various materials to change the design of a bicycle frame is the main topic of this research. Materials such as aluminum, titanium and carbon steel have specific features that can affect the strength, weight and response of a bicycle frame. This research involves designing a bicycle frame design using SolidWorks 2022, which is then used for simulation and strength analysis with Ansys. In this experiment, various materials were used, including aluminum alloy, titanium and carbon steel to measure the stress and deformation of each design and material tested. The purpose of this research is to study how the use of different types of materials when changing the design of a bicycle frame impacts the performance and strength of the bicycle. Tests were conducted through ansys simulation, with dynamic loads under conditions of daily bicycle use. The best data obtained in design 1 on titanium material, the top-tube section experienced a stress of 18.156 MPa and a deformation of 0.012078 mm. For aluminum material, the head-tube section experienced the lowest stress of 1.211 MPa and deformation of 0.0034886 mm. These results provide important insights for developing more efficient bicycle frame designs that can be tailored to user requirements and also impact the development of new materials in the bicycle industry aimed at improving the performance and durability of bicycle frames.